Effect of Resin Stages on the Dimensional Accuracy of Denture base cured by long and short curing method in a conventional water bath (Mustansiria Dental Journal, 2018)
Acrylic resin is the most widely used material in prosthetic dentistry and itsdimensional accuracy is most important factor in successfulness denture constructer.The aim of this study was to investigate the dimensional changes of denture baseacrylic cured by long and short curing method by using conventional water bath.60 maxillary wax bases were made and randomly assigned in 3 groups specimensaccording to the stringy, dough like and rubbery stages of the acrylic resin cured by:1-long curing cycle: curing the resin at 74 C° for 9 hours.2-Short curing cycle: processing the resin at 74 C° for 1 1/2 hour and at 100 C° for1/2 hour. Results were submitted to ANOVA and Turkey’s test and it showedthat in short curing cycle, the dough like stages presented values (0.193 mm)with statistically significant difference (P